A Systematic Literature Review on Work-Based Learning: Trends, Challenges, and Future Directions - Viona, Elsa; Afrianti, Heni (Perkumpulan Program Studi Doktor Pendidikan (PPSDP), 2024)
This study aims to explore the trends, challenges, and future directions of Work-Based Learning (WBL) across various educational and occupational contexts. By synthesizing findings from a wide array of studies, this review identifies key trends in WBL implementation, addresses the challenges faced by stakeholders, and highlights potential future research areas. The keywords used in this review were mainly: “Work-Based Learning,” “Technical Vocational Education and Training (TVET),” “apprenticeships,” “internships,” “cooperative education,” “practical learning,” and “vocational education.” This study explores all publications examining work based learning published from 1984-2024. The articles were selected according to the following criteria: (a) peer-reviewed original research published in international journal, (b) published in English, (c) in work-based learning context. Research articles selected were found through Scopus, Web of Science, Google Scholar, ERIC, and PubMed. Information is also collected using keywords identified using various search engines such as Google and AI-based GPT and analyzed using various research work analysis frameworks to identify, explore, and interpret trends, challenges, and future directions of work-based learning. The review covers WBL across multiple sectors, including vocational education, higher education, and professional development. The findings suggest that while WBL offers substantial benefits for students, educators, and employers, there are persistent challenges related to implementation, assessment, and equitable access.